Validitas LKPD Fase E Berbasis PBL Berdiferensiasi pada Materi Statistika - Isma, Isma Delita; Rismen, Sefna; Anggraini, Villia (Jurnal Riset Pembelajaran Matematika, 2024)
This study aims to produce a valid problem-based learning-based LKPD based on differentiation on statistics material for phase E students of SMAN 3 Padang. This type of research is R&D (Research and Development) development research with the Plomp development model. The results of the validation test of Problem Based Learning (PBL) based LKPD with differentiation reached a score of 84.3%, which is included in the very valid category. The data shows that PBL-based LKPD with differentiation on Phase E statistics material at SMAN 3 Padang is valid and can be used by teachers and students in the learning process.